Neuromuscular endplate pathology in recessive desminopathies: Lessons from man and mice. (23rd August 2016) - Durmuş, Hacer; Ayhan, Özgecan; Çırak, Sebahattin; Deymeer, Feza; Parman, Yeşim; Franke, Andre; Eiber, Nane; Chevessier, Frederic; Schlötzer-Schrehardt, Ursula; Clemen, Christoph S.; Hashemolhosseini, Said; Schröder, Rolf; et al.
Abstract : Objective: To assess the clinical, genetic, and myopathologic findings in 2 cousins with lack of desmin, the response to salbutamol in one patient, and the neuromuscular endplate pathology in a knock-in mouse model for recessive desminopathy. Methods: We performed clinical investigations in the patients, genetic studies for linkage mapping, exome sequencing, and qPCR for transcript quantification, assessment of efficacy of (3-month oral) salbutamol administration by muscle strength assessment, 6-minute walking test (6MWT), and forced vital capacity, analysis of neuromuscular endplate pathology in a homozygous R349P desmin knock-in mouse by immunofluorescence staining of the hind limb muscles, and quantitative 3D morphometry and expression studies of acetylcholine receptor genes by quantitative PCR. Results: Both patients had infantile-onset weakness and fatigability, facial weakness with bilateral ptosis and ophthalmoparesis, generalized muscle weakness, and a decremental response over 10% on repetitive nerve stimulation. Salbutamol improved 6MWT and subjective motor function in the treated patient. Genetic analysis revealed previously unreported novel homozygous truncating desmin mutation c.345dupC leading to protein truncation and consequent fast degradation of the mutant mRNA. In the recessive desminopathy mouse with low expression of the mutant desmin protein, we demonstrated fragmented motor endplates with increased surface areas, volumes, and fluorescence intensities in conjunction with increased α and γ acetylcholine receptor subunit expression in oxidative soleus muscle. Conclusions: The patients were desmin-null and had myopathy, cardiomyopathy, and a congenital myasthenic syndrome. The data from man and mouse demonstrate that the complete lack as well as the markedly decreased expression of mutant R349P desmin impair the structural and functional integrity of neuromuscular endplates.